2012
DOI: 10.1007/8904_2012_156
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Symptomatic Hyperammonemia in Children with Acute Lymphoblastic Leukemia Receiving Pegylated Asparaginase

Abstract: Asparaginase is a mainstay of treatment of childhood acute lymphoblastic leukemia. Pegylation of asparaginase extends its biological half-life and has been introduced in the newest treatment protocols aiming to further increase treatment success. Hyperammonemia is a recognized side effect of asparaginase treatment, but little is known about its incidence and clinical relevance. Alerted by a patient with severe hyperammonemia after introduction of the new acute lymphoblastic leukemia protocol, we analyzed blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 13 publications
2
50
0
2
Order By: Relevance
“…[82] Asparaginase therapy has also been associated with nonantibody-mediated infusion reactions that may result from spikes in serum ammonia levels. [83][84][85][86] Ammonia accumulation occurs as asparaginase facilitates the rapid conversion of asparagine and glutamine to aspartic acid and glutamic acid, with ammonia as the shared by-product of both reactions. [10] Symptoms of hyperammonemia are often transient in nature and can include nausea, vomiting, headache, dizziness, and rash.…”
Section: Infusion-related Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…[82] Asparaginase therapy has also been associated with nonantibody-mediated infusion reactions that may result from spikes in serum ammonia levels. [83][84][85][86] Ammonia accumulation occurs as asparaginase facilitates the rapid conversion of asparagine and glutamine to aspartic acid and glutamic acid, with ammonia as the shared by-product of both reactions. [10] Symptoms of hyperammonemia are often transient in nature and can include nausea, vomiting, headache, dizziness, and rash.…”
Section: Infusion-related Adverse Eventsmentioning
confidence: 99%
“…[10] Symptoms of hyperammonemia are often transient in nature and can include nausea, vomiting, headache, dizziness, and rash. [83,87,88] In patients receiving IV asparaginase, serum levels of ammonia have been shown to rise sharply following drug administration. Steiner et al [89] reported a significant elevation in ammonia levels in 10 patients 1 day after IV administration of native E. coli asparaginase (5000 IU/m 2 every 3 days), with recorded peak ammonia levels up to sevenfold the normal value.…”
Section: Infusion-related Adverse Eventsmentioning
confidence: 99%
“…9 Furthermore, it is possible that the nausea experienced by patients in the current series was a result of increased serum ammonia secondary to asparagine breakdown, as described by other investigators. 15,16 None of the current patients experienced lethargy or alteration in mental status suggestive of severe hyperammonemia, but systematic comparison of these results to symptoms seems justified. Finally, a direct comparison of the adverse effects experienced by patients with IM versus IV administration of EA should be performed.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, high dose steroids can lead to hyperammonemia by their catabolic action on skeletal muscle. Several other medications have been associated with increased ammonia (Table 2) [25][26][27][28].…”
Section: Urea Cyclementioning
confidence: 99%